GADAI TANAH PERTANIAN (SAWAH) MENURUT HUKUM ADAT SETELAH BERLAKUNYA UNDANG-UNDANG NO. 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA - Mantra I Gede Putu (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Agricultural land pawn transactions, especially rice fields, have actually existed for a long time in the midst of Indonesian society, especially rural communities, long before the issuance of the Agrarian Basic Law (UUPA). This happens in general, most of which is based on the economic insistence of the pawn giver (seller) such as the need for money to meet daily needs, financing schoolchildren and other urgent needs. This land lien transaction is only based on the principle of mutual trust between the parties, where between the granter (seller) of the pawn and the recipient (buyer) of the pawn only makes an agreement orally, without any written evidence or agreement under hand. The term of the pawn is based on the agreement between the granter (seller) of the pawn and the recipient (buyer) of the pawn. If the pawn giver is not able to make redemption of the pawn land in accordance with their agreement, then the pawn land (rice field) will remain under the control of the recipient (buyer) of the pawn until the granter (seller) of the pawn redeems it again. While Law No. 56 Prp of 1960 concerning the Determination of Agricultural Land Area, limiting the maximum land lien agreement can only be done for 7 (seven) years.